PH level has a strong impact on population dynamics of the yeast Yarrowia lipolytica and oil micro-droplets in multiphasic bioreactor. Issue 16 (4th July 2018) - Bouchedja, Doria Naila; Danthine, Sabine; Kar, Tambi; Fickers, Patrick; Sassi, Hosni; Boudjellal, Abdelghani; Blecker, Christophe; Delvigne, Frank
Abstract: The oleaginous yeast Yarrowia lipolytica has the ability to use oils and fats as carbon source, making it a promising cell factory for the design of alternative bioprocesses based on renewable substrates. However, such a multiphasic bioreactor design is rather complex and leads to several constraints when considering emulsification of the oil-in-water mixture, foaming and cell growth/physiology on hydrophobic substrate. This study aims to shed light on the effect of pH changes on the physico-chemical properties of the cultivation medium and on cell physiology. It was indeed observed that at a pH value of 6, cell growth rate and intracellular lipid accumulation were optimized. Additionally, foaming was significantly reduced. In order to avoid over foaming in bioreactor, without impairing cell physiology, the use of alternative processes that can only act on the physical structure of culture medium, seems to be an effective alternative to usual chemical anti-foam agents. Abstract : pH modulation promotes micro-droplets and yeast population efficiency in multiphasic bioreactor.